Design, simulation, and experimental analysis of a full-face motor bike helmet using composite material - Poudel, Bikalpa; Dumre, Bishnu; Acharya, Divyan; Bhattarai, Girish; Adhikari, Sunil (Journal of Innovations in Engineering Education, 2026)
Motorbike riders are highly exposed to severe accidents, and it is possible that the standard plastic helmets currently used in markets might not offer the required protection to them in these circumstances. To overcome this problem, this paper intends to design, simulate, fabricate, and conduct standard tests of a motorbike helmet made of composite materials to target producing a high ratio of strength-to-weight and an IS 4151 compliance helmet. The methodology starts with the selection of E glass fibers and polyester resin. The CAD modeling of the helmet of standard size 580 mm was performed in SolidWorks, and computational analysis was performed in ANSYS to assess the structural performance in real-world scenarios.  Also, an analytical comparison of the composite helmet with traditional ABS (Acrylonitrile Butadiene Styrene) helmets was conducted. The helmet was fabricated through the hand layup method and cured at normal atmospheric conditions. The manufactured helmet underwent the IS standard tests of rigidity, impact absorption, and resistance to penetration, and met all the required performance standards. Comparison of simulation results with the physical testing proved the validity of the design. On the whole, the project managed to create a motorbike helmet, which had a high level of structural strength and safety to be used in real-life situations.